BUSINESS STRATEGY AND COMPETITIVE ADVANTAGE a reinterpretation of michael. - Ateljević, Jovo ([S.l.] : ROUTLEDGE, 2023)
Michael Porter is recognized as one of the top authorities on corporate strategy and business competition. The historical review of strategic management clearly shows that Porter's research has bridged up two general paradigms (before and after the 1980s) thus helping both researchers and practitioners to better understand unanticipated global changes. His two generic strategies: costs and diversification, the two interdependent strategic options, are key in the context of the competitiveness of orthodox microeconomic theory. This is where Porter went further, constructing a popular value chain concept that provides the ability to disaggregate the key activities of business process in creating products and services in terms of cost analysis and value creation. This book is a collection of seven interconnected chapters that provides a coherent understanding of Michael Porter's contribution to the field of strategic management. It addresses key changes and challenges in the global business environment. The value chain concept has become highly applicable in both theory and practice. In the book, the authors offer an original interpretation of the Porters' research on strategic management in order to unravel or simplify his key theoretical concepts. It will be of interest to researchers, academics, practitioners, and students in the fields of strategic management and international business.
Keywords: BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / International / General; BUSINESS & ECONOMICS / Management; Strategic planning; Competition